Soil, water, nutrients and soil organic matter losses by water erosion as a function of soil management in the Posses sub-watershed, Extrema, Minas Gerais, Brazil - Bispo, Diêgo Faustolo Alves; Silva, Marx Leandro Naves; Pontes, Lucas Machado; Guimarães, Danielle Vieira; Marques, João José Granate de Sá e Melo; Curi, Nilton (Semina: Ciências Agrárias, 2017)
Knowledge of the quantity and quality of the material lost by soil erosion due to soil management is a basic need to identify land management zones in catchments. The aim of this study was to investigate the influence of soil management on the quantity and quality of soil material lost by erosion in the Posses sub-watershed, Municipality of Extrema, State of Minas Gerais, Brazil. Water and sediments lost by natural rainfall erosion were sampled from erosion plots located on a Red-Yellow Argisol (PVA) under the following systems: bare soil, subsistence farming (maize/beans/pumpkin/jack-beans/fallow), degraded pasture, well-managed pasture, and reforestation set up in 2013; and in a Litholic Neosol (RL): reforestation set up in 2008, bare soil, and native forest. Ca, Mg, K, P, N and soil organic matter (SOM) contents were determined in sediment and soil samples (at 0-5 cm depth) for the determination of the runoff enrichment ratios. Management influences soil losses more so than water losses. Minor losses were found in reforestation set up in 2013 (soil); in well-managed pasture (water); and in reforestations (nutrients and SOM). These losses tend to stability with time. The general sequence of nutrient losses was N > Ca > Mg > K > P in PVA; and N > Ca > K > Mg > P in RL. Loss rates of SOM and N followed the order: bare soil > subsistence farming > degraded pasture > well-managed pasture > reforestation, in PVA; and bare soil > native forest > reforestation, in RL. Reforestation and well-management pasture are effective conservation strategies in order to lower the erosion process in the Posses sub-watershed. Soil losses, as well as nutrients and organic matter losses were more influenced by soil management than water losses. The safeguarding native forest under Litholic Neosol is essential to the conservation of this pedoenvironment, especially in steep slopes.